Exacerbate or alleviate? impact of controlling shareholders' share pledging on over-investment - Geng, Huixia; Zhu, Hongbing; Lau, Wei Theng; Razak, Nazrul Hisyam Ab; Nor, Normaziah Mohd (Elsevier, 2024)
This paper investigates the relationship between controlling shareholders' share pledging and firm level over-investment. Utilizing Chinese A-share market data spanning 2007–2020, we find that firms with share pledging by controlling shareholders are more prone to over-invest, and the over-investment degree becomes severer as the pledging percentage increases. In addition, we observe this effect more pronounced in firms characterized by more concentrated ownership structure. Our findings still hold after the endogeneity disposal with a firm-fixed effect regression, Heckman two-stage regression with instrumental variables, the propensity score matching (PSM) and differences-in-differences (DID) approach. Furthermore, we observe that firms with controlling shareholders' share pledging tend to be concerned more with additional investments while neglecting maintenance investments and R&D investments. Combined with the motivation of controlling shareholders to gain substitute cash flow rights and convey good signals to the market, as well as the feasibility by using their dominate voting rights and pledged funds, it properly illustrates the mechanism through which controlling shareholders' share pledging impact over-investment, which meanwhile aggravates the principal-principal (PP) conflicts between controlling shareholders and minority shareholders. Consequently, our findings empirically demonstrate that signaling costs in signaling theory could be explicit conflicts in the agency theory, adding new empirical evidence for the relationship between signaling theory and agency theory.